2014
DOI: 10.1371/journal.pgen.1004580
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of SHANK Mutations in Autism Spectrum Disorders: A Gradient of Severity in Cognitive Impairments

Abstract: SHANK genes code for scaffold proteins located at the post-synaptic density of glutamatergic synapses. In neurons, SHANK2 and SHANK3 have a positive effect on the induction and maturation of dendritic spines, whereas SHANK1 induces the enlargement of spine heads. Mutations in SHANK genes have been associated with autism spectrum disorders (ASD), but their prevalence and clinical relevance remain to be determined. Here, we performed a new screen and a meta-analysis of SHANK copy-number and coding-sequence varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
515
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(541 citation statements)
references
References 58 publications
19
515
1
6
Order By: Relevance
“…CNVs and truncating mutations of SHANKs have been identified in almost 1% of ASD patients 185 , making the SHANK family of proteins central to the pathophysiology of autism.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…CNVs and truncating mutations of SHANKs have been identified in almost 1% of ASD patients 185 , making the SHANK family of proteins central to the pathophysiology of autism.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A review of recent studies in ASD using CMA or sequencing suggests that at least 0.5 % of ASD can be explained by deletions (0.16 %) or mutations (0.31 %) in SHANK3 [37]. In addition, up to 2 % of ASD with moderate-to-profound ID can be explained by loss of SHANK3 [38,39]. Men and women appear to be equally affected by PMS [40].…”
Section: Epidemiologymentioning
confidence: 99%
“…Soorya et al [10] used standardized methods to evaluate for ASD, which includes the Autism Diagnostic Interview-Revised [47], Autism Diagnostic Observation Schedule-G [48], and the Diagnostic and Statistical Manual of Mental Disorders-IV criteria [49], and found that 84 % of the patients with PMS in their study met the criteria for ASD. Patients with PMS are also commonly affected by ID, with approximately 75 % of patients showing severe-to-profound intellectual deficits [10,11,38,50].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Early genetic studies implicated SHANK family genes in both autism spectrum disorders (ASDs) and intellectual disability (3)(4)(5)(6). Increasing evidence supports a role for SHANK family genes in a broad spectrum of neuropsychiatric disorders (7).…”
Section: Introductionmentioning
confidence: 99%